2014
DOI: 10.1155/2014/602894
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Overview of Galactogogues

Abstract: Galactogogues are substances used to induce, maintain, and increase milk production, both in human clinical conditions (like noninfectious agalactias and hypogalactias) and in massification of production in the animal dairy industry. This paper aims to report the state of the art on the possible mechanisms of action, effectiveness, and side effects of galactogogues, including potential uses in veterinary and human medicine. The knowledge gaps in veterinary clinical practice use of galactogogues, especially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 134 publications
(176 reference statements)
1
42
0
Order By: Relevance
“…The influence of stress on plasma oxytocin and prolactin (the hormone essential for the lactation) concentrations on milk production was evaluated in 18 mothers of preterm infants. The results in the neonatal period; furthermore, it supports a good mother-baby relationship [1][2][3]. It has been clearly demonstrated that preterm infants receiving maternal milk have better outcomes, both nutritional (supply of polyunsaturated fat acids and proteins) and non-nutritional (reduced incidence of infections and atopic eczema) [4,5].…”
Section: The Correlation Between Stress and Hypogalactiamentioning
confidence: 87%
See 2 more Smart Citations
“…The influence of stress on plasma oxytocin and prolactin (the hormone essential for the lactation) concentrations on milk production was evaluated in 18 mothers of preterm infants. The results in the neonatal period; furthermore, it supports a good mother-baby relationship [1][2][3]. It has been clearly demonstrated that preterm infants receiving maternal milk have better outcomes, both nutritional (supply of polyunsaturated fat acids and proteins) and non-nutritional (reduced incidence of infections and atopic eczema) [4,5].…”
Section: The Correlation Between Stress and Hypogalactiamentioning
confidence: 87%
“…Physicians need to provide information regarding best practices for breastfeeding and, if necessary, they should indicate methods to support breast Nutrafoods (2015) tion of the myoepithelial cells that surround the alveoli and milk ducts, causing milk ejection; no adverse events), growth hormones (GH; somatotropin, mechanism of action not yet completely known, no adverse events), thyrotrophin-releasing hormone (TRH; stimulation of the secretion of thyroid-stimulating hormone and prolactin by the pituitary gland; some cases of iatrogenic hyperthyroidism and diaphoresis in mothers) and medroxyprogesterone (mechanism of action unknown, no adverse events except amenorrhea) [1,3].…”
Section: The Issue Of Hypogalactiamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies conducted on humans and animals suggested that this species has positive effects on milk secretion because it contains a mixture of flavonolignans. Silybin, the major constituent of silymarin, binds to cytosolic estrogen receptors determining phytoestrogenic activity [48,69,70].…”
Section: Fresh or Dried Leaves Fruitmentioning
confidence: 99%
“…They concluded that while the volume and composition of milk in poorly nourished women was Bsurprisingly good,^it was also often Bsuboptimal in quantity and in quality…^and noted that limited studies that supplemented such women resulted in improved milk output [138]. A recent overview of galactogogues published in a veterinary journal stated matter-of-factly that BBreastfeeding is influenced by nutritional and nonnutritional factors… that affect milk synthesis and secretion [139].^The idea that diet can make a difference in milk production seems much more acceptable in the animal lactation world than in the human lactation world.…”
Section: Maternal Nutrition: Does It Matter?mentioning
confidence: 99%